Kultur In vitro Tanaman Jeruk Pamelo (Citrus maxima Merr.) Menggunakan explant Biji Serta Deteksi Keberadaan Bakteri Liberobacter asiaticus pada Kalus yang Dihasilkan - PUTU BAMBANG IKA WINJALISTA; I GEDE PUTU WIRAWAN; MADE SRITAMIN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
In vitro culture of citrus plant Pamelo (Citrus maxima Merr.) Using Explant seeds as well as the detection of the presence of Bacteria Liberobacter asiaticus at Shoots are produced This research was begun with doing sample approachment in Kapal Village, Mengwi Sub-District, Badung regency and Sumerta Klod Village, East Denpasar Sub-District, Denpasar City and the culture in vitro was done in Implementing Technical Unit (UPT) Sumberdaya Genetika dan Biologi Molekuler Laboratory since October 2018 until January 2019. This research aim to recognize the response of pamelo orange's seed explant rather it will grow in based MS media which has been richen and got pamelo orange seed that is free from the infection of liberobcter asiaticus. The approachment of sample was based on the visualization of the plant, the plant which shows any indication of CVPD disease next will be known as 1st Sample and 2nd sample would be the plant which shows no indication of cvpd disease. The seed of each sample be cultured with MS media which has been richen, was maintained for 8 weeks after it's planted (mst). By the results of this research, it concludes that there's seed explant from both samples which grows without showing any indication of cvpd disease, but the result of DNA amplification from 1st sample that has been cultured in vitro after got UV transluminator visualization shows the existence of 1160 bp DNA ribbon which is belong to Liberobcter asiaticus. This shows that the sample has been infected by Liberobacter asiaticus, whereas can't be found in 2nd sample.